Subchronic effects of dietary selenium yeast and selenite on growth performance and the immune and antioxidant systems in Nile tilapia Oreochromis niloticus. Issue 97 (February 2020) - Chen, Hongxing; Li, Jian; Yan, Liang; Cao, Jinling; Li, Dan; Huang, Guo-Yong; Shi, Wen-Jun; Dong, Wu; Zha, Jinmiao; Ying, Guang-Guo; Zhong, Huan; Wang, Zhifang; et al.
Abstract: Selenium is an essential element but toxic at high levels in animals. The effects of Se on growth performance and the immune system in Nile tilapia remain inconclusive. In this study, Nile tilapia Oreochromis niloticus was fed on selenium yeast (Se(Y))- and selenite (Se(IV))-enriched feed at 0, 3, 6, and 12 μg/g (dry wt) for 45 and 90 d. The growth, bioaccumulation, biochemical markers related to antioxidant, immunological, nervous and digestive systems were evaluated in various fish tissues (liver, intestine, kidney, muscle, brain, spleen, gills). The results showed that the accumulation of Se(Y) was 1.3–2 folds of Se(IV) in most tissues. The growth of tilapia was enhanced by both Se(Y) and Se(IV) at 3 μg/g after 90 d, with Se(Y) better than Se(IV) in tilapia feed. After 45 d, the levels of lipid peroxidation, the activity of the antioxidant enzymes, and the transcriptional levels of the immune related genes ( IL-1β, IFN-γ and TNF-α ) and stress proteins ( HSP70 and MT ) were enhanced in all treatments, except that of MT in the 12 μg/g Se(Y) group. In addition, both Se species inhibited the activity of acetylcholinesterase (AChE) in the brain and one digestive enzyme α-glucosidase (α-Glu) in the intestine at 12 μg/g. However, after 90 d, the effects on most biochemical markers were less pronounced, implying a possible acclimation after prolonged duration. The results demonstrate Se is beneficial to O. niloticus at low levels and toxic at elevated levels. The immunostimulation by Se might be greatly weakened after long term feeding Se-enriched feed. This study helps to better understand the effects of Se on the antioxidant and immune systems and to establish the optimal Se levels in the feed and duration for O. niloticus . Highlights: Se increases the transcripts of IL-1β, IFN-γ and TNF-α in O. niloticus after 45 d feeding. Se enhances the mRNA levels of the stress proteins HSP70 and MT. Se(Y) and Se(IV) enhance the growth of tilapia at low level but inhibit it at high level after 90 d of feeding. High level of Se adversely affects the antioxidant, nervous and digestive systems of O. niloticus. The immunostimulation of Se might be weakened after prolonged feeding.